Studi Fenomenologi: Makna Quarter-Life Crisis bagi Mahasiswa Pendidikan Matematika - Hapsari, Aisyah Three; Noverli, Muthiah Fildzah (Papanda, 2025)
Quarter-life crisis can have different meanings for each individual. The purpose of this study was to uncover the meaning of quarter-life crisis from the perspective of Mathematics Education students based on their personal experiences. The method used was descriptive qualitative with a phenomenological approach and four 6th semester students of the Mathematics Education Study Program at a university in West Java Province were selected purposively based on the criteria that the participants had truly experienced a quarter-life crisis and were able to explain the experience in depth. Data were collected through in-depth semi-structured interviews, then analyzed using the Miles method which included data reduction, data presentation, and drawing conclusions. The results showed that each participant interpreted the quarter-life crisis differently, some interpreted it as a golden age, a phase of self-growth, confusion about the future, and early adulthood after we passed through adolescence which was all good. Thus, it is concluded that the meaning of quarter-life crisis from the perspective of Mathematics Education students varies depending on what they experience and feel. This study also shows that there is pressure that arises from various sources, both from within the participants, academics, and the surrounding environment, including family expectations and social pressure after graduation which are the causes of the quarter-life crisis in Mathematics Education students.